Penguatan Keterampilan Guru Bahasa Inggris Melalui Pelatihan Integratif dengan Pendekatan Multimodal - Farikah, Farikah; Ekawati, Mursia; Hamdani, Rifki; Sisviana, Ety; Ma’ruf, Amar (Panrannuangku Jurnal Pengabdian Masyarakat, 2025)
to improve the competence of elementary school teachers in Magelang Regency in facing the challenges of the 2022 Curriculum. This training includes providing materials, mentoring, and simulation of best practices to strengthen teachers' understanding of multimodal learning approaches, compiling teaching materials, and utilising technology. As a result, teachers can design and adapt multimodal-based teaching materials using text, audio, video, and images effectively, increasing student engagement. This program also encourages collaboration between teachers, creating a network of mutually supportive learning communities. The outputs of the activity include the publication of scientific articles, proceedings, workshops, teaching modules, and mentoring. Although access to technology is an obstacle, this activity has a positive impact on improving teacher competence and the quality of learning. The success of the program is the basis for further development, including expanding participants, integrating the latest technology, and ongoing mentoring, thus contributing to improving the quality of English education at the elementary school level.